The traditional Maranaw governance system descriptive issues and imperatives for Philippine public administration - Nolasco, Liberty Ibañez (2004)
The traditional Maranaw governance system (TMGS) is regarded as an intricate yet sophisticated system. The Adat and Qur'an are the foundation of the functions and processes of central and local governance structures. This article thoroughly discusses its identity and continuity. Furthermore, TMGS places importance on family, relatives, and society and community. The central government bears the concept of a nation or the Bangsa Moro. The author points out that since TMGS is not a closed system, the colonization of the Philippines brought about the integration of formal institutions of power and authority (FIPA) to the once traditional structures of the power and authority of the Maranaws.
Keywords: Igorot (Philippine people); Maranao ( Philippine people); Governance